Stories from the English riverbank: How riparian communities interpret, articulate and action water resource sustainability - Gearey, Mary (European Journal of Sustainable Development, 2016)
To effectively communicate sustainable policies and strategies at a societal level we first need to understand how water users themselves comprehend the challenges that management practitioners face. Understanding the different lifeworld perspectives of citizens who live and work alongside their water resources allows policy makers and practitioners to target messages which accord with individual’s own experiences. Nexus governance thinking recognizes the integral role of water in cementing sustainable economic development and societal continuity, yet fails to capture the granularity of individual perceptions and responses with regards to water resources management. Through empirical fieldwork with residents in three UK waterside communities, interrogating a range of management issues, the research has begun to build a picture of where water ‘sits’ within individual lifeworlds. Cataloguing these local knowledges, responses and actions provides data to determine what types and what temporality of changes to water resources people will accept in support of sustainability.These insights reveal modes of community resilience which correspond with the key sustainability messages around changing water conditions and demonstrate the myriad ways water users have interpreted and responded to these articulations. Keywords: Nexus governance, water resources management, sustainability, community resilience